Anxiolytic, antidepressant, and antistress activities of the aqueous extract of Cinnamomum tamala Nees and Eberm in rats - Upadhyay G.; Khoshla S.; Kosuru R.; Singh S. (My University, 2025)
Objective: The current study was designed to explore anxiolytic, antidepressant, and antistress actions of Cinnamomum tamala (CT) leaves (aqueous extract) in rats. Materials and Methods: Behavioral procedures of anxiety, depression, and stress were assessed in rats. CT (100, 200, and 400 mg/kg) was given once a daily for 7 days via oral route and the efficacy was matched by those elicited by lorazepam (1 mg/kg, p.o.), imipramine (10 mg/kg, p.o.), and Withania somnifera (100 mg/kg, p.o.) for anxiolytic, antidepressant, and antistress studies, respectively. Standard drugs were given 1 time, 30 min preceding the behavioral trials. Results: One-way analysis of variance followed by Newman-Keuls multiple comparison test was employed to analyze the results. P < 0.05 was considered statistically significant as compared to control. CT at 400 mg/kg produced an antianxiety effect equivalent to lorazepam, in the elevated plus maze, open field, and social interaction tests among selected doses of the CT. CT at 400 mg/kg also induced an antidepressant activity similar to imipramine, in the behavioral despair, learned helplessness test, and tail suspension among selected doses of the CT. Moreover, CT at 400 mg/kg produced a significant antistress effect comparable to W. somnifera in water immersion-restraint stress by decreasing ulcer index, adrenal gland weight, and by normalizing the plasma levels of corticosterone, glucose, cholesterol, and triglyceride levels when related to stress control. Conclusion: The study shows that among the different CT doses, CT at 400 mg/kg possesses significant anxiolytic, antidepressant, and anti-stress effects and has therapeutic beneficial for the management of psychological ailments. © 2016 Indian Journal of Pharmacology Published by Wolters Kluwer - Medknow.